Medicine–food homology bioactives in Parkinson’s disease: multi-target oxidative-stress modulation and translation to dietary supplements - Wang, Meng; Zhang, Yizhu; Wu, Qiong; Ma, Sijia; Wang, Chao; Sang, Jiajia (Frontiers in Nutrition, 2025)
BackgroundNo proven disease-modifying therapy exists for Parkinson’s disease (PD), and prior single-target antioxidants have shown limited, unsustained benefits, highlighting the need for safe multi-target strategies.ObjectiveTo synthesize how medicine–food homology (MFH) compounds from Traditional Chinese Medicine (TCM)—polysaccharides, saponins/triterpenoids, polyphenols, carotenoids, and aromatic phenylpropanoids—modulate oxidative stress and PD-related neurodegeneration, and to outline formulation routes toward dietary-supplement development.MethodsWe searched PubMed, Web of Science Core Collection, Embase (Ovid), and the Cochrane Library from inception through August 1, 2025 with prespecified concept blocks (“Parkinson’s disease,” “oxidative stress,” Nrf2/ARE, NF-κB, PI3K/Akt, autophagy, and MFH terms). English-language in-vitro, invertebrate, and PD-specific rodent studies, selected epidemiology, and formulation/dose/regulatory reports were narratively appraised; no meta-analysis or tool-based risk-of-bias scoring was performed.ResultsMFH compounds converge on Nrf2/ARE activation, NF-κB suppression, autophagy promotion, and mitochondrial stabilization; nano-/micro-delivery may improve bioavailability and brain exposure in preclinical models. Evidence is predominantly preclinical, with heterogeneous methods and sparse PD-specific randomized trials; epidemiologic signals are suggestive but non-causal. PD-specific oxidative stress arises from dopamine auto-oxidation, neuromelanin–iron catalysis, and complex-I hypofunction; Latest studies further bind these to ferroptosis-linked lipid peroxidation. Clinical evidence remains sparse and PK-limited for MFH actives (e.g., curcumin, EGCG); dose–response, safety monitoring (including liver signals for catechins), and regulatory constraints frame translation.ConclusionMFH compounds are promising, hypothesis-generating candidates for adjunctive nutrition in PD, pending clinical dose–response and long-term safety validation. No clinical efficacy has been established.